ANALISIS HUBUNGAN MOTIVASI DAN HASIL BELAJAR SISWA KELAS VII SMP N 8 PEKANBARU - Fitriani, Fitriani; Suryawati, Evi; Fauziah, Yuslim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The purpose of this study is to determine the relationship of motivation with science learning outcomes of Grade VII students of SMP N 8 Pekanbaru. This research was conducted at SMP Negeri 8 Pekanbaru in November 2019. This type of research is descriptive. the population in this study were all students of class VII SMP 8 Pekanbaru. While the sample in this study was 15% of VII grade students of SMP 8 Pekanbaru taken random sampling using udian. The research data were sourced from primary and secondary data, primary data were obtained from motivational questionnaires that were distributed to students while secondary dta was taken from the recapitulation of the teacher's daily test scores. Based on the results of the analysis of motivation and student learning outcomes VII grade SMPN 8 Pekabaru it can be seen that the motivation of students overall motivation refers to an average of 3.36 with a medium category. the correlation is 51% Key Words: Motivation, Learning Outcomes